Regarding: “Inspiratory muscle training improves performance of a repeated sprints ability test in professional soccer players” - Ribeiro G.S. (2019)
© 2019The Journal of Bodywork & Movement Therapies recently published an article by Silva et al., entitled “Inspiratory muscle training improves performance of a repeated sprints ability test in professional soccer players” (Silva et al., 2019). After close reading we find that the new findings of Silva et al., (2019) are relevant and provide a promising indication that IMT can improve the performance of young male soccer players. However, some additional important points must be considered when interpreting these positive findings.